Natural Small Molecule Drugs from Plants - Du, Guan-Hua (Springer Singapore, 2018)
This book discusses 120 types of natural, small-molecule drugs derived from plants. They are grouped into 7 parts according their clinical uses, such as drugs for cardiovascular diseases, for metabolic diseases, for neuropsychiatric diseases, for immune-mediated inflammatory diseases, anti-tumor drugs, and drugs for parasites and bacterial infection. Each chapter systematically summarizes one drug, including its physicochemical properties, sources, pharmacological effects and clinical applications. To help readers understand the drug better, the research and pharmacological activity for each drug is also described, which serves as a salutary lesson for future drug development. Written by frontline researchers, teachers and clinicians working in field of pharmacy and pharmacology it provides an overview of natural, small-molecule drugs derived from plants for researchers in the field.